2020
DOI: 10.3389/fbioe.2020.00590
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cervical Cancer With Parametrial Invasion on Whole-Tumor Dynamic Contrast-Enhanced Magnetic Resonance Imaging Combined With Whole-Lesion Texture Analysis Based on T2- Weighted Images

Abstract: Purpose: To evaluate the diagnostic value of the combination of whole-tumor dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and whole-lesion texture features based on T2-weighted images for cervical cancer with parametrial invasion. Materials and Methods: Sixty-two patients with cervical cancer (27 with parametrial invasion and 35 without invasion) preoperatively underwent routine MRI and DCE-MRI examinations. DCE-MRI parameters (K trans , K ep , and V e) and texture features (mean, skewness, ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(28 reference statements)
0
6
0
2
Order By: Relevance
“…( 35 ) and Li et al. ( 36 ) studied the relationship between parametrial invasion, a high-risk factor for cervical cancer, and DCE-MRI parameters, and found that the quantitative parameter values ​​of primary lesions in the infiltrating group were significantly higher than those in the non-infiltrating group. This was similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…( 35 ) and Li et al. ( 36 ) studied the relationship between parametrial invasion, a high-risk factor for cervical cancer, and DCE-MRI parameters, and found that the quantitative parameter values ​​of primary lesions in the infiltrating group were significantly higher than those in the non-infiltrating group. This was similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…the rate constant, K ep ) и внеклеточное объемное соотношение (англ. extracellular volume, V e ) [59]. В результате ROC-анализа были установлены пороговые значения (cut-off) для наиболее информативных визуализационных и текстурных показателей для оценки параметральной инвазии: пороговое значение K trans ≥ 0,286 мин -1 может стать оптимальным порогом для установления вовлеченности в процесс параметральной клетчатки и использоваться в клинической практике (AUC = 0,788; чувствительность = 0,839; специфичность = 0,657).…”
Section: а Bunclassified
“…По своей диагностической эффективности она превзошла комбинированное использование K trans + Энергия (AUC = 0,727, чувствительность = 0,806, специфичность = 0,657) и Энтропия + Энергия (AUC = 0,619, чувствительность = 0,548, специфичность = 0,771, соответственно). Наиболее информативной в оценке инвазии явилась комбинация всех трех параметров -K trans + Энтропия + Энергия (AUС = 0,925, чувствительность = 0,935, специфичность = 0,829), что обосновывает сочетанное применение мультипараметрической МРТ и текстурного анализа в рамках предоперационного обследования пациенток [59].…”
Section: а Bunclassified
“…It is a common malignant tumor all over the world, with a high incidence, which has seriously affected women's physical and mental health. [1,2] In recent years, chemotherapy has gradually become one of prior treatment methods for cervical carcinoma. [3][4][5] It has been reported that low-dose chemotherapeutics could increase the sensitivity of radiotherapy in cervical carcinoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical carcinoma, a malignant tumor that develops in the cervix, is mainly related to long-term infection. It is a common malignant tumor all over the world, with a high incidence, which has seriously affected women's physical and mental health [1,2] . In recent years, chemotherapy has gradually become one of prior treatment methods for cervical carcinoma [3–5] .…”
Section: Introductionmentioning
confidence: 99%